Promoting Participation in Daily Activities Through Reablement: A Qualitative Study. (27th January 2020) - Magne, Trine A.; Vik, Kjersti
Abstract : A well-known prediction is that the growing elderly population will place a strain on our healthcare systems. At the same time, healthcare is becoming increasingly patient-centered and individualized, with the patient becoming an active participant rather than a mere object of healthcare. The need for change may be met by using a reablement service, utilizing the rehabilitation mindset through home-based services. Rehabilitation and reablement aim to provide opportunities for individuals to participate to a maximum of their potential. This study is part of a larger research project exploring different aspects of reablement in municipalities. It aims to describe how older adults engage in daily activities within the context of reablement and to explore participation in daily activities. A qualitative design was chosen, and the study is explorative in nature due to limited research on participants' experience with reablement. Ten older adults age 70 to 94 years old were recruited and interviewed. The interviews were transcribed verbatim and analyzed using systematic text condensation (STC) strategies. This study provides insights on how older adults experience participation in daily activities and important aspects for performing these activities and living independently as long as possible. Based on the older adults' experiences, three main themes were identified when receiving reablement. First, what to achieve with reablement and feeling a sense of security to participate in daily activities. Second, how to carry out wanted activities using different skills and last, how the social network is important for enabling active living. This calls for healthcare workers to address and facilitate these in reablement. Our findings show the importance of collaborating with the social network and strengthening participation in daily activities to establish and develop existing reablement services.